TEST DESK FOR EDDY-CURRENT PROBE CHECKING - Zakrevskiy, Alexander (Proceedings of National Aviation University (archive), 2012)
The paper presents a test desk and the results of the experiment on the validity of the “Eddy-current probe – control object” system mathematical model. The “Eddy-current probe – control object” system mathematical model takes into account finite control object dimensions and its face of curvature absence. The paper focuses on the influence of the control object diameter and the distance from Eddy-current probe to Control object on the Eddy-current probe relative inductance curve dependence.